Women's self-employment: An act of institutional (dis)integration? A multilevel, cross-country study - Klyver, Kim; Nielsen, Suna Løwe; Evald, Majbritt Rostgaard (Journal of Business Venturing, 2013)
In this paper we investigate the extent to which gender equality disintegrates women's self-employment choice (compared to that for men) and whether this is contingent upon a country's development stage and industries. We rely on symbolic interactionism to argue that employment choices emerge from an interactive conversation between individual and social institutional processes. Using data from 61 countries, we find that overall gender equality is associated with the gender gap in men's and women's self-employment choices and that this association depends upon the country's development stage and industries. Contributions are made to women's entrepreneurship and institutional theory.